Harmonization of Religious Harmony in a Hadith Perspective - Bambang Utomo; Damanhuri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Bukhari Hadith Number 6531 All the narrators in the hadith sanad, totaling 4 narrators, are all qualified: tshiqah (trusted). All the transmitters each met with a transmitter who had the status of their teacher, thus their sanad was muttasil; The hadith explains that togetherness is something that is commanded. Allah to Muslims. In each of His commands, Allah always uses the jama'i (communal) form such as Ya ayyuhalladina A'manu (O you who believe) not the infiradi (individual) form Ya ayyuhal mu'min (O you who believe). Togetherness is important because by always being together and living side by side in society, we can exchange thoughts, life experiences and opinions which will be useful when we face a problem. Together, various problems can be solved and overcome.